Claims of Contemporary Political Representation Theory - Mateusz Zieliński (Politeja)
In this work, I will attempt to address the question of what lies ahead for the theory of political representation after the “constructivist turn” that has dominated this theoretical field in recent years. In doing so, I draw upon the influential theory of Michel Saward, whose contributions have ignited inter-paradigmatic debates involving, among others, feminist authors and theorists advocating for radical democratic theory. In the article, I explore both Saward’s own arguments and the key propositions presented by his opponents. I emphasise that his assumptions not only necessitate a reformulation of the technical aspects of representation (its sources of legitimacy and principles of accountability) but also reveal the need for a theoretical reflection on the effects of new forms of “representative claims”. As I will endeavour to demonstrate, these claims lead us to a debate on the nature of “political relationships”, which I define as situations in which two or more political subjectivities mutually condition each other.